Survival Mechanism Pekerja Migran Indonesia Purna Tugas - Wahyudi, Irfan; Ida, Rachmah; Koesbardiati, Toetik; Kinasih, Sri Endah; Murti, Delta Bayu (Journal of Governance and Administrative Reform, 2022)
Abstract Since the WHO declared the COVID-19 pandemic on December 1, 2019, the first group to be laid off were migrant workers. For migrant workers who are laid off one way is to return to their country of origin, including Indonesian Migrant Workers (PMI). For PMIs who work undocumented, they must be deported. PMI departed undocumented, mostly from Sampang, Madura, East Java. The number of PMI from Sampang who have been deported since COVID 19 took place was 886 people. To respond to this situation, research on improving the survival mechanism of the post-employee PMI in marketing the products of Micro, Small and Medium Enterprises (MSMEs) through the use of social media in the district of Sampang, Madura, East Java, contributes to their survival. This research method begins with conducting a Focus Group Discussion to map out the difficulties of post-employee PMI in marketing products so that they can find the right marketing solutions, especially through the use of social media. The FGD involved stakeholders among retired PMIs such as the Indonesian Migrant Workers Union (SBMI), the industry office, BP2MI, the cooperative service, village heads, religious leaders from Nahdlatul Ulama (NU) and youth organizations. Furthermore, in-depth interviews and observations were carried out. The last stage is to analyze the data that correlates the data with the theory used in reviewing the survival mechanism, namely community empowerment. The result of the research is that the recycled handicraft products of garbage and chips, crackers and various types of food using mass media as a medium to disseminate local product marketing content will be optimized by residents, so that local residents get sufficient correct and useful information as a reference. One of the uses of PMI's post-duty mass media is making the Shopee application. They have learned to make products for social media, starting with compiling video scripts, designing marketing posters, and packaging. Shopee has various types of promo programs that buyers can enjoy, such as discount promos and free shipping. Thus, the retired PMI will be trained to produce and market their business as their survival mechanism. Keywords: survival mechanism, former Indonesian migrant workers, micro small and medium enterprise Abstrak Sejak ditetapkan pandemi COVID-19 oleh WHO pada tanggal 1 Desember 2019, menjadi kelompok pertama yang diberhentikan adalah pekerja migran. Bagi pekerja migran yang diberhentikan salah satu jalan kembali ke negara asal, termasuk Pekerja Migran Indonesia (PMI). Bagi PMI yang berkerja secara undocumented, mereka harus dideportasi. PMI berangkat secara undocumented, terbanyak adalah kabupaten Sampang Madura Jawa Timur. PMI asal Sampang yang dideportasi, sejak COVID 19 berlangsung sebesar 886 orang. Untuk merespon situasi ini maka penelitian peningkatan survival mechanism PMI purna tugas dalam memasarkan produk Usaha Mikro Kecil dan Menengah (UMKM) melalui pemanfaatan media sosial di kabupaten Sampang Madura Jawa Timur memberikan kontribusi untuk kelangsungan hidup mereka. Metode penelitian ini diawali dengan melakukan Focus Group Discussion untuk memetakan kesulitan PMI purna tugas dalam memasarkan produk sehingga dapat menemukan solusi pemasaran yang tepat, terutama melalui pemanfaat media sosial. FGD melibatkan stakeholder dikalangan PMI purna tugas seperti Serikat Buruh Migran Indonesia (SBMI), dinas perindustrian, BP2MI, dinas koperasi, kepala desa, tokoh agama Nahdlatul Ulama (NU) dan karang taruna. Selanjutnya dilakukan indepth interview dan observasi. Tahap terakhir melakukan analisa data yang mengkorelasikan antara data dengan teori yang digunakan dalam mengkaji survival mechanism, yaitu pemberdayaan masyarakat. Hasil penelitian adalah produk kerajinan daur ulang sampah dan keripik, kerupuk serta berbagai jenis makanan dengan pemanfaatan media massa sebagai medium untuk menyebarkan konten pemasaran produk lokal akan dioptimalkan oleh warga, sehingga warga setempat mendapatkan kecukupan informasi yang benar dan bermanfaat sebagai rujukan. Pemanfaatan media massa PMI purna tugas salah satunya membuat aplikasi Shopee. Mereka sudah belajar membuat produk untuk media sosial yang dimulai dengan menyusun naskah video, desain poster pemasaran, dan packaging. Shopee mempunyai berbagai jenis program promo yang dapat dinikmati oleh para pembeli, seperti promo potongan dan gratis ongkir. Dengan demikian, PMI purna tugas akan terlatih untuk memproduk dan memasarkan usaha mereka sebagai survival mechanism mereka. Kata kunci: mekanisme kelangsungan hidup, mantan pekerja migran Indonesia, usaha mikro kecil dan menengah